Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor di Kota Batam - Muhamad Tedy Lum; Poniman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The objective of this study was to investigate the impact of various factors that influence compliance with motor vehicle tax obligations. The aforementioned elements comprise the execution of Samsat Keliling, the E-Samsat Program, and tax sanctions. This study employed a quantitative methodology, with the primary means of data collection being the distribution of questionnaires. In this investigation, the population was 442,092. One hundred individuals were sampled utilizing the Slovin formula, which introduced a 10% margin of error. The data analysis methodology incorporates a variety of linear analysis techniques, and SPSS version 29 is utilized for data processing. Motor Vehicle Taxpayer Compliance is significantly impacted by the concurrent implementation of Samsat Keliling, the E-Samsat Program, and tax sanctions, according to the findings of this study. The impact of motor vehicle taxpayer compliance is notably influenced by the implementation of Samsat Keliling and the E-Samsat Program. Tax sanctions, meanwhile, have little impact on the compliance of motor vehicle taxpayers. Keywords: Implementation of Samsat Keliling, E-Samsat Program, Tax Sanctions